Traffic‐Related Air Pollution and Carotid Plaque Burden in a Canadian City With Low‐Level Ambient Pollution - Johnson, Markey (J Am Heart Assoc, 2020)
BACKGROUND: The association between fine particulate matter and cardiovascular disease has been convincingly demonstrated. The role of traffic‐related air pollutants is less clear. To better understand the role of traffic‐related air pollutants in cardiovascular disease development, we examined associations between NO(2), carotid atherosclerotic plaque, and cardiometabolic disorders associated with cardiovascular disease. METHODS AND RESULTS: Cross‐sectional analyses were conducted among 2227 patients (62.9±13.8 years; 49.5% women) from the Stroke Prevention and Atherosclerosis Research Centre (SPARC) in London, Ontario, Canada. Total carotid plaque area measured by ultrasound, cardiometabolic disorders, and residential locations were provided by SPARC medical records. Long‐term outdoor residential NO(2) concentrations were generated by a land use regression model. Associations between NO(2), total carotid plaque area, and cardiometabolic disorders were examined using multiple regression models adjusted for age, sex, smoking, and socioeconomic status. Mean NO(2) was 5.4±1.6 ppb in London, Ontario. NO(2) was associated with a significant increase in plaque (3.4 mm(2) total carotid plaque area per 1 ppb NO(2)), exhibiting a linear dose‐response. NO(2) was also positively associated with triglycerides, total cholesterol, and the ratio of low‐ to high‐density lipoprotein cholesterol (P<0.05). Diabetes mellitus mediated the relationship between NO(2) and total carotid plaque area (P<0.05). CONCLUSIONS: Our results demonstrate that even low levels of traffic‐related air pollutants are linked to atherosclerotic plaque burden, an association that may be partially attributable to pollution‐induced diabetes mellitus. Our findings suggest that reducing ambient concentrations in cities with NO(2) below current standards would result in additional health benefits. Given the billions of people exposed to traffic emissions, our study supports the global public health significance of reducing air pollution.